Ultrastructural and physiological responses of potato (Solanum tuberosum L.) plantlets to gradient saline stress - Gao, Hui-Juan; Yang, Hong-Yu; Bai, Jiang-Ping; Liang, Xin-Yue; Lou, Yan; Zhang, Juan-Lian; Wang, Di; ZHANG, JIN-LIN; Niu, Shu-Qi; Chen, Yinglong (Frontiers in Plant Science, 2015)
Salinity is one of the major abiotic stresses that impacts plant growth and reduces the productivity of field crops. Compared to field plants, test tube plantlets offer a direct and fast approach to investigate the mechanism of salt tolerance. Here we examined the ultrastructural and physiological responses of potato (Solanum tuberosum L. c.v. ‘Longshu No. 3’) plantlets to gradient saline stress (0, 25, 50, 100 and 200 mM NaCl) with two consequent observations (two and six weeks, respectively). The results showed that, with the increase of external NaCl concentration and the duration of treatments, (1) the number of chloroplasts and cell intercellular spaces markedly decreased, (2) cell walls were thickened and even ruptured, (3) mesophyll cells and chloroplasts were gradually damaged to a complete disorganization containing more starch, (4) leaf Na and Cl contents increased while leaf K content decreased, (5) leaf proline content and the activities of catalase (CAT) and superoxide dismutase (SOD) increased significantly, and (6) leaf malondialdehyde (MDA) content increased significantly and stomatal area and chlorophyll content decline were also detected. Severe salt stress (200 mM NaCl) inhibited plantlet growth. These results indicated that potato plantlets adapt to salt stress to some extent through accumulating osmoprotectants, such as proline, increasing the activities of antioxidant enzymes, such as CAT and SOD. The outcomes of this study provide ultrastructural and physiological insights into characterizing potential damages induced by salt stress for selecting salt-tolerant potato cultivars.